2013
DOI: 10.1002/cav.1530
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of traditional Chinese shadow play‐Piying art from tangible interaction

Abstract: Piying, the world's intangible culture heritage, is a characteristic Chinese folk shadow play and one of the origins of modern movie. The spirit of traditional Piying is to express rich emotion and stories through impromptu action change by professional artists. Now Piying gradually fades away in people's lives, encountering the risk of extinction. We focus on transforming the traditional Piying play into an interactive system, which can be seamlessly performed by ordinary people and bring a strong sense of im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Additionally, based on subjective and objective feedback from user experiments, the system exhibits high usability (SUS score of 84.4), which can effectively reduce the difficulty of creating shadow puppet images. In contrast to previous methods based on parameterization [6,7] and deep learning [8], which can effectively help ordinary users create high-quality shadow puppet images from three aspects: User drawing, inspiration stimulation and content generation. The quality of creative results has been significantly enhanced due to algorithmic improvements and the development of high-quality training datasets.…”
Section: Figure 12: Some Shadow Puppet Images Created By Usersmentioning
confidence: 97%
See 1 more Smart Citation
“…Additionally, based on subjective and objective feedback from user experiments, the system exhibits high usability (SUS score of 84.4), which can effectively reduce the difficulty of creating shadow puppet images. In contrast to previous methods based on parameterization [6,7] and deep learning [8], which can effectively help ordinary users create high-quality shadow puppet images from three aspects: User drawing, inspiration stimulation and content generation. The quality of creative results has been significantly enhanced due to algorithmic improvements and the development of high-quality training datasets.…”
Section: Figure 12: Some Shadow Puppet Images Created By Usersmentioning
confidence: 97%
“…Previous research predominantly concentrates on shadow puppetry performances [4][5][6], with less focus on the intelligent creation of shadow puppet images. The intelligent creation of shadow puppetry poses numerous challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Virtual reality (VR) and more generally extended realities (XR), are now widely used in the domain of cultural heritage as they provide the means of document- ing, recovering and presenting historical contexts [2]. Beyond historical material such as artefacts, buildings, monuments, or cities, XR also allows to represent intangible cultural heritage with many different human activities such as crafting [16], artistic expression, [1,20,4], or traditional sports [23].…”
Section: The Use Of Virtual Reality For Cultural Heritage Preservationmentioning
confidence: 99%
“…They were engaged effectively in the experience and developed a basic understanding of puppetry, alongside the interactive technology that also improved their creativity and social skills. Shi and colleagues combined characteristics of Chinese folk culture to design a digital shadow puppet, and developed an interactive system that exploited Kinect-based interactions and sensors to capture children's movements, the goal being to help them express their emotions with shadow puppets [32]. Their assessment showed that the system helps children develop a fundamental understanding of shadow puppetry.…”
Section: Interactive Technology For Puppetry Appreciationmentioning
confidence: 99%